2007
DOI: 10.1103/physrevb.76.195107
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of the mixed oxideαFeCrO3

Abstract: 2We have investigated the electronic and magnetic properties of the mixed oxide α-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 33 publications
5
36
0
Order By: Relevance
“…According to literatures, 9,17,18 the absorption band at 1.8 eV corresponds to excitation of valence electrons at Cr t 2g and/ or O 2p states to the empty Fe t 2g * state. This picture is further supported by a recent theoretical study based on density functional theory (DFT) calculations with a Hubbard U-term, which concludes that the band-gap of CrFeO 3 is reduced to 1.9 eV.…”
Section: O 3 Solid-solution Filmsmentioning
confidence: 93%
See 1 more Smart Citation
“…According to literatures, 9,17,18 the absorption band at 1.8 eV corresponds to excitation of valence electrons at Cr t 2g and/ or O 2p states to the empty Fe t 2g * state. This picture is further supported by a recent theoretical study based on density functional theory (DFT) calculations with a Hubbard U-term, which concludes that the band-gap of CrFeO 3 is reduced to 1.9 eV.…”
Section: O 3 Solid-solution Filmsmentioning
confidence: 93%
“…6,7 It is a charge transfer (CT) insulator with a bandgap (E g ) of 2.1 eV between occupied O 2p state and empty Fe 3d upper Hubbard band. 6,8,9 a-Cr 2 O 3 is chosen as a counterpart material because of the absence of miscibility gap in binary phase diagram with a-Fe 2 O 3 . 10 It is known as a mixed CT and Mott-Hubbard insulator with E g ¼ 3.3 eV.…”
Section: O 3 Solid-solution Filmsmentioning
confidence: 99%
“…It is one of the few crystals whose band gap values are commonly used to gauge the level of correlation of the methods. [57] UHF often yields band gaps that are too large, [58] LSDA and SGGA on the other hand give very small or even null band gap. [59] B3LYP [57] gives a band gap of 3.2 eV comparable to the experimental value of 2.0 eV.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[57] UHF often yields band gaps that are too large, [58] LSDA and SGGA on the other hand give very small or even null band gap. [59] B3LYP [57] gives a band gap of 3.2 eV comparable to the experimental value of 2.0 eV. We have calculated its HI atomic charges and spin-densities for α-Fe 2 O 3 with different Hamiltonians, namely UHF, PBE [39] and PBE0 [60] considering 8-6411G* and 8-411G* basis sets [50] for Fe and O, respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Indeed spin orbit interactions in the actinides can be thought of as an effective magnetic field -the main difference being that the effective magnetic field depends on the electron momentum. In addition, it has recently been shown that the importance of spin-orbit interactions varies in a systematic way as one moves across the actinides [8]. In particular, measurements of the branching ratios for 4d → 5f 5/2 and 4d → 5f 7/2 transitions in the actinides using TEM electron energy loss spectroscopy suggest that spin-orbit effects increase dramatically in importance as one moves from U to Pu and Am.…”
mentioning
confidence: 99%